2012
DOI: 10.1051/0004-6361/201117709
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and sodium in the globular cluster M 4

Abstract: Context. The abundance inhomogeneities of light elements observed in globular clusters (GCs), and notably the ubiquitous Na-O anti-correlation, are generally interpreted as evidence that GCs comprise several generations of stars. There is an on-going debate as to the nature of the stars, which produce the inhomogeneous elements, and investigating the behavior of several elements is a way to shed new light on this problem. Aims. We aim at investigating the Li and Na content of the GC M 4, that is known to have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(140 citation statements)
references
References 50 publications
5
133
1
Order By: Relevance
“…The detection of Li-rich stars in M30 adds to the ever-growing list of globular clusters that host Li-rich stars. Monaco et al (2012) reported the detection of a Li-rich dwarf in M4 with a Li abundance compatible with the predicted primordial lithium abundance based on standard BBN (Coc et al 2013). In addition to M4, there are at least three other globular clusters that seem to harbour stars with Li abundances similar to the primordial Li abundance, NGC 6752 (Shen et al 2010) and 47 Tuc (D'Orazi et al 2010), or well above the primordial Li abundance, NGC 6397 (Koch et al 2011).…”
Section: A Li-rich Subgiantmentioning
confidence: 76%
“…The detection of Li-rich stars in M30 adds to the ever-growing list of globular clusters that host Li-rich stars. Monaco et al (2012) reported the detection of a Li-rich dwarf in M4 with a Li abundance compatible with the predicted primordial lithium abundance based on standard BBN (Coc et al 2013). In addition to M4, there are at least three other globular clusters that seem to harbour stars with Li abundances similar to the primordial Li abundance, NGC 6752 (Shen et al 2010) and 47 Tuc (D'Orazi et al 2010), or well above the primordial Li abundance, NGC 6397 (Koch et al 2011).…”
Section: A Li-rich Subgiantmentioning
confidence: 76%
“…Its logarithmic ( 7 Li) non-local thermodynamic equilibrium (NLTE) surface abundance is ≈4.2, i.e., an order of magnitude above the maximum main-sequence Li abundance, however, the currently accepted primordial Li abundance (2.72 dex; Cyburt et al 2008), is at odds with the WMAP satellite measurements, implying a primordial Li production three to five times higher than observed (e.g., Sbordone et al 2010). The hypothesis of Li pollution from a previous generation of stars has also found further evidence from recent detections of Li-rich dwarfs in globular clusters (Koch et al 2010;Monaco et al 2012). Therefore, a detailed study of the surface lithium of a key star may also shed some light on these discrepancies.…”
Section: Introductionmentioning
confidence: 89%
“…While it is fully representative of the remainder of the GC giant and TO stars in terms of metallicity, α-element abundance ratios, and stellar parameters, it has a Li abundance about 100 times higher than any other NGC 6397 stars. With an exceptional abundance of log( 7 Li/H)+12 = 4.2 (assuming non-LTE), it is one of the stars with the highest Li ever observed (Koch et al , 2012, and only very few other dwarf or giant stars show comparable levels of enhancement (Reyniers & Van Winckel 2001;Deliyannis et al 2002;Monaco et al 2012;Adamów et al 2012). What produced such a high Li abundance in a TO star of a GC?…”
Section: Introductionmentioning
confidence: 99%